Modified quasilinearization algorithm for optimal control problems with nondifferential constraints and general boundary conditions - Gonzalez, S.; Rodriguez, S. (Journal of optimization theory and applications, 1986)
This paper considers the numerical solution of the problem of minimizing a functional I, subject to differential constraints, nondifferential constraints, and general boundary conditions. It consists of finding the state x(t), the control u(t), and the parameter pi so that the functional I is minimized while the constraints are satisfied to a predetermined accuracy. The modified quasilinearization algorithm (MQA) is extended, so that it can be applied to the solution of optimal control problems with general boundary conditions, where the state is not explicitly given at the initial point. The algorithm presented here preserves the MQA descent property on the cumulative error.